The Influence of Work Discipline on the Performance of Civil Servants at the Department of Industry and Trade of West Papua Province - Deselina Hurulean; Kaleb Yohan Karubaba; Nikolina Balia (Scieclouds Publishing, 2026)
This study examines the influence of work discipline on the performance of civil servants at the Department of Industry and Trade of West Papua Province. Employee performance remains a central concern in public sector management because government institutions must deliver services that are reliable, accountable, and responsive to community and economic development needs. Work discipline is positioned in this study as a behavioral foundation that enables employees to comply with organizational rules, use working time effectively, follow work standards, maintain vigilance, and demonstrate ethical conduct. A quantitative approach with an explanatory research design was employed. The population consisted of 156 civil servants, all of whom were included as respondents through a saturated sampling technique. Primary data were collected using a structured questionnaire measured on a five-point Likert scale, while secondary data were obtained from organizational documents, government reports, regulations, and relevant literature. Data were analyzed using IBM SPSS Statistics Version 26 through validity and reliability tests, classical assumption tests, descriptive analysis, simple linear regression, coefficient of determination, and t-test hypothesis testing. The findings show that work discipline has a positive and significant effect on employee performance. The regression result indicates that higher work discipline is associated with improved employee performance, while the coefficient of determination shows that work discipline explains 33.6% of the variance in employee performance. The study concludes that strengthening work discipline is an important strategy for improving civil servant performance, but it must be supported by leadership, supervision, motivation, competence development, and a broader fair organizational culture.